До історії етнографічних досліджень Криму: Олександр Федорович Музиченко - Непомнящий, А. (Народна творчість та етнографія, 2007)
Using documents of Chernihiv oblast State Archives Department in Nizhyn and Myzychenko’s poorly investigated activity in the field of the Crimean studies the author of the article opens unknown pages of outstanding Ukrainian pedagogue’s biography which relate to studying ethnography of the Crimean Bulgarians. The author reconstituted all repertoire of Oleksandr Muzychenko’s ethnographic bibliography that relates to studying folklore of the Crimean Bulgarians.